Parental beliefs about children's emotions within and across sociocultural contexts - Brown, Deon W.; Dunsmore, Julie C. (Frontiers in Developmental Psychology, 2025)
Beliefs about emotion may guide parents' socialization behaviors and shape the overall family environment. Research specifically addressing parental beliefs about children's emotions has expanded in the past 3 decades. Much of this research addresses variations in emotion-related parental beliefs within and across sociocultural contexts, demonstrating how these beliefs may represent a confluence of the macrosystem and microsystem, or m (ai)crosystem. In this paper, we review the body of research on parental beliefs about emotions. We describe the array of emotion-related parental beliefs that have been studied and discuss associations of these beliefs with parenting behaviors and child outcomes that are linked to positive youth development. We extend the field's consideration of sociocultural contexts for parental beliefs by addressing how cultural socialization, racial socialization, and gender socialization may influence and be influenced by parents' beliefs about children's emotions. We identify areas of strength in the literature and gaps in knowledge that are important areas for growth. We conclude by suggesting future directions for theory and research on the role of parental beliefs in family processes and positive youth development.